Mechanical thrombectomy for acute stroke in childhood: how much does restricted diffusion matter? - Ladner, Travis R (BMJ Case Rep, 2014)
Mechanical thrombectomy holds promise for children with large cerebral arterial occlusions, although there are few reports in this population. We report a case of retrievable stent-assisted mechanical thrombectomy in a 5-year-old with basilar artery occlusion, despite late presentation and extensive initial diffusion-weighted imaging (DWI) restriction. This resulted in successful Thrombolysis in Cerebral Infarction 2B reperfusion and excellent clinical outcome. At 6-week follow-up he was completely back to baseline with no residual deficits (pediatric stroke outcome measure=0, modified Rankin scale=0). At 3-month follow-up the patient has not had any recurrent stroke or concern for stroke-like symptoms. We review the literature on mechanical thrombectomy and DWI changes in acute stroke in early to middle childhood (<12 years old).